PERTIMBANGAN HUKUM HAK PERWALIAN ANAK AKIBAT PERCERAIAN ORANG TUA DI WILAYAH HUKUM PENGADILAN TINGGI AGAMA BANTEN - Karmawan, Karmawan (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
Divorce is a complex situation that often affects child custody and welfare. In the jurisdiction of the Banten High Religious Court, determining post-divorce child custody rights requires careful legal consideration in accordance with the principles of Islamic law and the best interests of the child. This paper aims to examine the relevant legal considerations in determining child custody rights as a consequence of parental divorce. This research concludes that the process of determining post-divorce child custody rights in the jurisdiction of the Banten High Religious Court requires a holistic and sensitive approach to the interests and welfare of the child. In this context, a deep understanding of the principles of Islamic law, as well as wisdom in handling conflicts between parents, is key in safeguarding the rights and welfare of children involved in divorce.